Penerapan Metode Electre dan Simple Additive Weigthing (SAW) Sistem Pendukung Keputusan Penerima Beasiswa Berprestasi Dompet Dhuafa Waspada Medan - Sofiyatul Adawiyah; Ilka Zufria; Raissa Amanda Putri (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
As technology develops, decision support systems are also widely used in various fields, for example banking, education, agriculture and other fields. Dompet Dhufa provides assistance to students who are outstanding but economically weak. Currently, the poor people's wallet is alert to still using manual selection. Selectors are only given a few days to decide who is entitled to receive the proposed scholarship, so the selection process cannot be carried out properly and correctly because the time given is not efficient with selection carried out manually. Therefore, it is necessary to carry out new innovations that develop appropriate technological tools, namely designing decision support to determine student scholarship recipients, applying Electre and the Simple Additive Weighting (SAW) method in shortening the selection of solutions to problems for scholarship recipients. Research on the Application of the Electre and Simple Additive Weighting Methods (SAW) to design the working capacity of a tool is defined as the ability of the selecting party. An example of unit time (hours) yield is a representation of an application obtained by comparing the initial system with the final system. The advantage of this application is that it makes it easier for the selection team to input data on students who take part in high-achieving scholarships and can then be selected fairly and speed up predictions of scholarship recipients.